2020
DOI: 10.1161/circgen.120.003117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Cardiac Involvement in Danon Disease

Abstract: Background - The X-linked Danon disease (DD) manifests by severe cardiomyopathy, myopathy, and neuropsychiatric problems. We designed this registry to generate a comprehensive picture of clinical presentations and outcome of patients with Danon disease (DD) in cardiomyopathy centers throughout Europe. Methods - Clinical and genetic data were collected in 16 cardiology centers from 8 European countries. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…However, because of its X‐linked nature and the hemizygous male status, DD arises 1 to 2 decades earlier in men, with onset typically by adolescence. 45 , 46 , 47 Women have far less common extracardiac manifestations than men, making the clinical diagnosis challenging and often delayed in the absence of family history or genetic testing. 45 , 47 , 48 DD cardiomyopathy is typically rapidly progressive.…”
Section: Hypertrophic Heart Disease Caused By X‐linked Genetic Variantsmentioning
confidence: 99%
“…However, because of its X‐linked nature and the hemizygous male status, DD arises 1 to 2 decades earlier in men, with onset typically by adolescence. 45 , 46 , 47 Women have far less common extracardiac manifestations than men, making the clinical diagnosis challenging and often delayed in the absence of family history or genetic testing. 45 , 47 , 48 DD cardiomyopathy is typically rapidly progressive.…”
Section: Hypertrophic Heart Disease Caused By X‐linked Genetic Variantsmentioning
confidence: 99%
“…This patient did not have extra-cardiac findings of Danon disease at the time of the last follow-up at age 15 years. While this may reflect incomplete penetrance of extra-cardiac findings, studies have reported that extra-cardiac manifestations can be absent or delayed in those with secondary CMP, including those with Danon disease 27 . This reflects our rationale for including secondary CMP genes and also Tier 2 genes in our study since variants in these genes can contribute to the cardiac phenotype 28 , 29 .…”
Section: Discussionmentioning
confidence: 98%
“…In particular, among the 57 patients evaluated (30 males and 27 females), 53% had a heart failure hospitalization, 27% underwent heart transplantation or received an LV assist device, and 30% of patients died during follow-up. Moreover, in this cohort, SCD occurred in three female patients, and appropriate implantable cardioverter-defibrillator (ICD) interventions for ventricular tachycardia/fibrillation were evidenced in six patients, underlying the high risk of SCD in this population (98).…”
Section: Prognosis and Risk Of Sudden Cardiac Deathmentioning
confidence: 90%
“…Heart failure and arrhythmia constitute the leading cause of morbidity and mortality in patients with Danon disease. Recently, data from a multicenter European registry have shown that Danon disease runs a malignant course in both genders, due to cardiac complications (98). In particular, among the 57 patients evaluated (30 males and 27 females), 53% had a heart failure hospitalization, 27% underwent heart transplantation or received an LV assist device, and 30% of patients died during follow-up.…”
Section: Prognosis and Risk Of Sudden Cardiac Deathmentioning
confidence: 99%